Measuring the Impact of E-Portfolio Assessment on the Moroccan Undergraduate EFL Students’ Reading Skill at the University of Moulay Ismail: A Case Study - Assiya Ait Mama (Yayasan Visi Intan Permata, 2023)
Motivated by the conviction that formative assessment can foster positive changes in reading instruction, this study seeks to investigate the impact of e-portfolio as a formative assessment tool, on the reading skill of semester two EFL students at the Department of English Studies in Moulay Ismail University of Meknes, Morocco. A pre-posttest experimental design is adopted in this study. The sample of the study consists of thirty-two students who are randomly assigned into two groups: an experimental group with a number of sixteen respondents who have received an e-portfolio assessment and a control group of sixteen participants who had traditional standardized testing. The two groups received different assessment methods but had similar reading comprehension instruction. A reading proficiency Test was administered to the comparative groups on two occasions before and after the experiment. The reading proficiency test constitutes of three multilevel tasks of Literal, Inferential, and Evaluative comprehension. The test scores serve as criteria for statistical comparisons between the comparative groups. The results show that the experimental group demonstrated improved reading comprehension in all three tasks, whereas the control group upgraded only in the literal comprehension task. Overall results of the current study are consistent with past research that provides support for the use of e-portfolio to assess and monitor students’ reading proficiency. The findings and conclusions derived from the present study can serve as a starting point for such an assessment to take place. Decision-makers and teachers can thus promote the use of e-portfolios in language teaching and learning as a formative assessment.